Who benefits from training: big guy or small fry? - Hashim, Junaidah; Wok, Saodah (Emerald Group Publishing Limited, 2013)
This study aims to measure the effectiveness of training schemes and levy utilization in terms of cognitive gain and skills changes through increased knowledge and skills intensity to improve job performance among large companies and SMEs in Malaysia.